2015
DOI: 10.1063/1.4907194
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless shocks driven by 800 nm laser pulses generate high-energy carbon ions

Abstract: We present experimental studies on ion acceleration from diamond-like carbon (DLC) foils irradiated by 800 nm, linearly polarized laser pulses with peak intensity of 1.7 Â 10 19 W/cm 2 to 3.5 Â 10 19 W/cm 2 at oblique incidence. Diamond-like carbon foils are heated by the prepulse of a high-contrast laser pulse and expand to form plasmas of near-critical density caused by thermal effect before the arrival of the main pulse. It is demonstrated that carbon ions are accelerated by a collisionless shock wave in sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Furthermore, recent achievement of mono-energetic proton acceleration by collisionless ES shock produced by ultrahigh-intensity laser system [84][85][86] shows a possibility to apply the collisionless shock to several applications including medical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent achievement of mono-energetic proton acceleration by collisionless ES shock produced by ultrahigh-intensity laser system [84][85][86] shows a possibility to apply the collisionless shock to several applications including medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical simulation has revealed ion acceleration at a relativistic ES shock generated in an overdense plasma due to reflection of ions in the upstream region by the shock front [75][76][77][78][79][80][81][82][83], and mono-energetic proton acceleration by ES shock has been shown experimentally [84][85][86]. These mono-energetic protons have a potential to be used in several applications including medical treatment [87].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we suggested using the relativistic transparency for shock generation by circularly polarized (CP) pulses [21], where hot-electron recirculation is not available. Regarding the effects of transmittance on shock formation, there have been seemingly contradictory results; Zhang et al could obtain a quasimonoenergetic carbon beam of ∼7.5 MeV from an * mshur@unist.ac.kr opaque plasma irradiated by an LP pulse but could not do so in transparent plasma [22]. Meanwhile, Lecz et al observed that shock ion acceleration was more efficient in semitransparent plasmas with 20-30% transmittance [23].…”
Section: Introductionmentioning
confidence: 97%
“…Consequently the circularly polarized pulse can be more efficient than the linear one in shock ion acceleration under the limited pulse energy. In our scheme, controlled prepulse energy and duration are utilized for target explosion [30]. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was suggested to use an electrostatic shock [23][24][25][26][27][28][29][30] for ion acceleration, where a laser pulse with moderate power and a near-critical target are used. In this system, a stable electrostatic shock with a high Mach number (>1.5) is formed in a similar way as in Ref.…”
Section: Introductionmentioning
confidence: 99%